Performance evaluation of standalone double axis solar tracking system with ‎maximum light detection MLD for telecommunication towers in Malaysia - Ahmed Mohamed Abdulmula; Kamaruzzaman Sopian; Lim Chin Haw; Ahmad Fazlizan (Institute of Advanced Engineering and Science, 2019)
This paper is performed to investigate the performance of ‎dual-axis solar tracking system with maximum light detection for off-grid telecommunication towers under weather conditions in Malaysia. The studied system consists of High-efficiency heterojunction intrinsic thin (HIT) film solar modules ‎coupled with state-of-the-art dual-axis maximum light detection (MLD) solar ‎tracking system. The ‎investigation method is based on the analyzed the daily actual data record for both the average power output of ‎the photovoltaic system and the ‎state of charge of batteries in four months ‎under different weather conditions as a function of time. Based on the results obtained ‎the use of HIT solar modules with MLD dual ‎axis solar tracking system has high performance effective under ‎Malaysian weather.‎ The study also presented the detailed investigated system description.